2017
DOI: 10.3747/pdi.2017.00004
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal Equilibration Test Reference Values Using A 3.86% Glucose Solution during the First Year of Peritoneal Dialysis: Results of a Multicenter Study of a Large Patient Population

Abstract: The results of the study provide PET-3.86% reference values for the beginning of PD that can be used to classify PD patients into transport classes and monitor them over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…A close positive association between peritoneal transport rates and glucose absorption has also been reported, both when using 2.27% (2.5%) or 3.86% (4.5%) PD fluid (e.g. patients with fast peritoneal transport rates also have faster glucose absorption) (31)(32)(33). During a 4-h peritoneal equilibration test (using 2 L of 2.5% PD fluid) glucose absorption was 20.3 AE 0.4 g in patients with low peritoneal transport rates, 26.0 AE 0.1 g in the low-average transporter group, 31.1 AE 0.1 g in the high-average transporter group, and 35.4 AE 0.3 g in patients with high peritoneal transport rates (27).…”
Section: Glucose Load and Effect On Nodm In Pd Patientsmentioning
confidence: 63%
“…A close positive association between peritoneal transport rates and glucose absorption has also been reported, both when using 2.27% (2.5%) or 3.86% (4.5%) PD fluid (e.g. patients with fast peritoneal transport rates also have faster glucose absorption) (31)(32)(33). During a 4-h peritoneal equilibration test (using 2 L of 2.5% PD fluid) glucose absorption was 20.3 AE 0.4 g in patients with low peritoneal transport rates, 26.0 AE 0.1 g in the low-average transporter group, 31.1 AE 0.1 g in the high-average transporter group, and 35.4 AE 0.3 g in patients with high peritoneal transport rates (27).…”
Section: Glucose Load and Effect On Nodm In Pd Patientsmentioning
confidence: 63%
“…(2) Intrinsic low UF -variation in FWT Clinical evidence and implications. PSTR explains less than 20% of the variation in the inter-individual differences in 50 Australia/New Zealand 3702 0.69 +0.12 Smit et al 51 Netherlands 154 0.73 +0.10 Lambie et al 42 UK, Canada, Korea 595 0.71 +0.12 Mehrotra et al 45 USA 10,142 0.65 +0.12 La Milia et al 53 Italy 758 0.73 +0.12 Shi et al 52 China 320 0.62 +0.11…”
Section: Clinical Evidence and Implicationsmentioning
confidence: 99%
“…It is not possible to give a generally applicable cut-off value, however, as multicenter studies, such as those shown in Table 2, show that there is a clear centre effect, and possible a regional effect seen when measuring PSTR, likely due to different methods for measuring blood and dialysate creatinine levels, including adjustment for glucose concentration in the dialysate. 42,[45][46][47][48][49][50][51][52][53] Ideally, centres would establish their own normal range (a further argument for undertaking routine measurements in all newly established patients at a standardized time point), but it is recognized that this may not be practical, especially for many smaller centres. One solution to this would be the national reporting of membrane function tests, as is achieved by the ANZDATA registry.…”
Section: ) Fast Pstr -Local Inflammation But Recognition Of Other Mec...mentioning
confidence: 99%
“…Incidence rate of the outcome measure "peritoneal membrane deterioration" could not be identified in registry reports and this outcome was therefore individually searched in published clinical reports on repeated peritoneal equilibration tests (PET). The PET assesses time-dependent changes in dialysate volume and solute levels (e.g., creatinine or sodium) during the dwell, given as ultrafiltration, as ratios of dialysate to plasma (D/P) solute levels (e.g., creatinine), and as sodium sieving or free water transport (17)(18)(19)(20)(21)(22). "Peritoneal membrane deterioration" was defined as ultrafiltration loss, increase of D/P creatinine transport ratio, and/or decrease of sodium dip.…”
Section: Methodsmentioning
confidence: 99%